tcR: an R package for T cell receptor repertoire advanced data analysis - Nazarov, Vadim I.; Pogorelyy, Mikhail V.; Komech, Ekaterina A.; Zvyagin, Ivan V.; Bolotin, Dmitry A.; Shugay, Mikhail; Chudakov, Dmitry M.; Lebedev, Yury B.; Mamedov, Ilgar Z. (BMC bioinformatics, 2015)
Background The Immunoglobulins (IG) and the T cell receptors (TR) play the key role in antigen recognition during the adaptive immune response. Recent progress in next-generation sequencing technologies has provided an opportunity for the deep T cell receptor repertoire profiling. However, a specialised software is required for the rational analysis of massive data generated by next-generation sequencing. Results Here we introduce tcR, a new R package, representing a platform for the advanced analysis of T cell receptor repertoires, which includes diversity measures, shared T cell receptor sequences identification, gene usage statistics computation and other widely used methods. The tool has proven its utility in recent research studies. Conclusions tcR is an R package for the advanced analysis of T cell receptor repertoires after primary TR sequences extraction from raw sequencing reads. The stable version can be directly installed from The Comprehensive R Archive Network ( http://cran.r-project.org/mirrors.html ). The source code and development version are available at tcR GitHub ( http://imminfo.github.io/tcr/ ) along with the full documentation and typical usage examples.